Fostering Students’ Creative and Ethical Character through Green Chemistry Modules in Project-Based Learning in Wetland Ecosystems - Suyidno Suyidno; Suryajaya Suryajaya; Qamariah Qamariah; Misbah Misbah; Nor Farahwahidah Abdul Rahman (Universitas Lambung Mangkurat, 2026)
competency in life and career skills in the 21st century. However, schools in wetland ecosystems have not optimized this character development because appropriate learning modules are not yet available. Therefore, this study aims to analyze the effectiveness of a project-based learning (PBL)-oriented green chemistry module in fostering students' creative and ethical character in wetland ecosystems. This study is part of a research and development program using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model focused on the Development, Implementation, and Evaluation (DIE) stages. This study involved 15 students in the limited test and 33 students in the field test. The researchers collected data using a character questionnaire instrument, a project outcome assessment, and documentation. Then they analyzed the data descriptively using the n-gain test and paired-samples t-tests or Wilcoxon tests. The results showed that the distribution of student character categories increased from lower categories to higher categories. In the limited test, students who were originally in the good and very good categories all increased to the very good category. In the field test, students who were initially distributed across the good and very good categories (81.25%) shifted to the very good category (90.63%). Students' creative and moral character increased significantly in both the limited test and the field test with a moderate increase category (p < 0.05; n-gain = 0.54), and students' project results were in the very good category. Thus, the implementation of the PBL-oriented green chemistry module has proven effective in fostering students' creative and moral character in wetland ecosystems.